Crash-worthy speedster. - Fallows, James (Atlantic Monthly)
Examines IBM's unheralded OS/2 2.0 operating system. Disk operating system (DOS) and Bill Gates' fortunes; Operating more than one program at a time; Windows, the graphic environment introduced by Microsoft; Memory required for operation of OS/2; Differences between OS/2 2.0 and DOS; Cost of OS/2 2.0 and equipment needed; More.